Incorporation of tetanus-epitope into virus-like particles achieves vaccine responses even in older recipients in models of psoriasis, Alzheimer’s and cat allergy - Zeltins, Andris; West, Jonathan; Zabel, Franziska; El Turabi, Aadil; Balke, Ina; Haas, Stefanie; Maudrich, Melanie; Storni, Federico; Engeroff, Paul; Jennings, Gary T.; Kotecha, Abhay; Stuart, David I; et al. (npj vaccines, 2017)
Monoclonal antibodies are widely used to treat non-infectious conditions but are costly. Vaccines could offer a cost-effective alternative but have been limited by sub-optimal T-cell stimulation and/or weak vaccine responses in recipients, for example, in elderly patients. We have previously shown that the repetitive structure of virus-like-particles (VLPs) can effectively bypass self-tolerance in therapeutic vaccines. Their efficacy could be increased even further by the incorporation of an epitope stimulating T cell help. However, the self-assembly and stability of VLPs from envelope monomer proteins is sensitive to geometry, rendering the incorporation of foreign epitopes difficult. We here show that it is possible to engineer VLPs derived from a non human-pathogenic plant virus to incorporate a powerful T-cell-stimulatory epitope derived from Tetanus toxoid. These VLPs (termed CMV TT ) retain self-assembly as well as long-term stability. Since Th cell memory to Tetanus is near universal in humans, CMV TT -based vaccines can deliver robust antibody-responses even under limiting conditions. By way of proof of concept, we tested a range of such vaccines against chronic inflammatory conditions (model: psoriasis, antigen: interleukin-17), neurodegenerative (Alzheimer’s, β-amyloid), and allergic disease (cat allergy, Fel-d1), respectively. Vaccine responses were uniformly strong, selective, efficient in vivo , observed even in old mice, and employing low vaccine doses. In addition, randomly ascertained human blood cells were reactive to CMV TT -VLPs, confirming recognition of the incorporated Tetanus epitope. The CMV TT -VLP platform is adaptable to almost any antigen and its features and performance are ideally suited for the design of vaccines delivering enhanced responsiveness in aging populations. Noninfectious disease: Virus-like particles with wide-ranging applications A fusion of tetanus vaccine and cucumber mosaic virus produces a therapeutic that can be adapted to treat multiple inflammatory diseases. Led by John Foerster, of University of Dundee, and Martin Bachmnann, of the University of Oxford and the University of Bern, scientists were able to take the protein coat of cucumber mosaic virus and incorporate a tetanus vaccine-derived protein structure known to stimulate the immune system. In doing so, they produced a vaccine that could accept additional stimulatory proteins and generate targeted immune responses. The team tested their therapeutic on mice and found it raised antibody levels thought to be beneficial in Alzheimer’s disease. The vaccine also showed positive results in models of psoriasis and cat allergy. More research is needed; however, many patients stand to gain from more affordable treatments for inflammatory disease.